Atomic scale insight into the decomposition of nanocrystalline zinc hydroxynitrate toward ZnO using Mn2+ paramagnetic probes - Vlaicu, Ioana D.; Stefan, Mariana; Radu, Cristian; Culita, Daniela C.; Radu, Dana; Ghica, Daniela (Frontiers in Chemistry, 2023)
Layered zinc hydroxynitrate (ZHN), with the chemical formula Zn5 (OH)8 (NO3)2·2H2O, exhibits a range of special properties such as anion-exchange and intercalation capacity, as well as biocompatibility, making it attractive for a large variety of applications in fields from nanotechnology to healthcare and agriculture. In this study nanocrystalline ZHN doped with 1,000 ppm Mn2+ was prepared by two synthesis methods (coprecipitation and solid state reaction) using similar environment-friendly precursors. The complex morpho-structural [X-ray diffraction, scanning and transmission electron microscopy, textural analysis] and spectroscopic [Fourier transform infrared and electron paramagnetic resonance (EPR)] characterization of the two ZHN nanopowders showed similar crystalline structures with Mn2+ ions localized in the nanocrystals volume, but with differences in their morphological and textural characteristics, as well as in the doping efficiency. ZHN obtained by coprecipitation consists of larger nanoplatelets with more than two times larger specific surface area and pore volume, as well as a dopant concentration than in the ZHN sample obtained by solid state reaction. The thermal stability and the on-set of the structural phase transformation have been investigated at atomic scale with high accuracy by EPR, using Mn2+ as paramagnetic probes. The on-set of the ZHN structural phase transformation toward ZnO was observed by EPR to take place at 110°C and 130°C for the samples prepared by coprecipitation and solid state reaction, respectively, evidencing a manganese induced local decrease of the transformation temperature. Our results contribute to the selection of the most appropriate ZHN synthesis method for specific applications and in the development of new green, cost-effective synthesis routes for Mn2+ doped nano-ZnO.